Telehealth care before and during COVID-19: trends and quality in a large health system. Issue 4 (4th October 2022) - Luna, Paulina; Lee, Megan; Vergara Greeno, Rebeca; DeLucia, Nikki; London, Yollanda; Hoffman, Pamela; Burg, Matthew; Harris, Kristie; Spatz, Erica S; Mena-Hurtado, Carlos; Smolderen, Kim G
Abstract: Objective: COVID-19 accelerated telehealth use to ensure care delivery, but there is limited data on the patient perspective. This study aimed to examine telehealth visit uptake before and during COVID-19 and correlates of patient satisfaction and interest in future telehealth visits. Materials and Methods: This was a cross-sectional observational study between October 2019 and April 2020. Participants included patients who completed satisfaction surveys following telehealth visits. Results: A total of 8930 patients completed the satisfaction survey using 4-point Likert Scales. Multivariable, hierarchical, cumulative logit models were constructed to examine correlates of satisfaction with quality of care and interest in future telehealth visits. Most patients were satisfied with the patient portal, video quality, and instructions (92.7%–96.8%). Almost half reported saving 1–2 h (46.9%). Correlates positively associated with quality of care and interest in future telehealth visits were ease of patient portal (odds ratio [OR], 1.43, 95% confidence interval [CI], 1.30–1.58; OR, 1.56, 95% CI, 1.41–1.73, respectively), video quality (OR, 1.62, 95% CI, 1.50–1.75; OR, 1.26, 95% CI, 1.16–1.37, respectively), instructions (OR, 5.62, 95% CI, 5.05–6.26; OR, 1.80, 95% CI, 1.62–2.01, respectively), and time saved (>4 h: OR, 1.69, 95%, CI, 1.22–2.34; OR, 3.49, 95% CI, 2.47–4.93, respectively). Being seen after the COVID-19 surge in telehealth (OR, 0.76, 95% CI, 0.63–0.93) or by providers with higher visit volume (OR, 0.71, 95% CI, 0.60–0.85) was associated with lower interest in future telehealth visits. Conclusions: Patients expressed relatively high satisfaction levels with telehealth. Better technical quality, quality of instructions, and greater time saved were associated with higher satisfaction ratings. To maintain interest in future telehealth use and improve the patient experience, we must enhance the quality of telehealth delivery platforms and instructions provided to patients. Lay Summary: COVID-19 accelerated telehealth use to ensure care delivery, but there are limited data on the patient perspective. Therefore, this study focused on factors impacting patient satisfaction with telehealth. We found that better technical quality, quality of instructions before the visit, and greater time saved by having a telehealth appointment rather than in-person were associated with higher satisfaction ratings. Given that telehealth will likely remain an important aspect of healthcare delivery beyond the COVID-19 pandemic, we must enhance the quality of telehealth delivery platforms and instructions provided to patients to maintain interest in future telehealth use and improve the patient experience.